(3JYQjaGJ GdYdhe hehVhYGJgGs - (3YHO Gddg Hf YeQ Hf eMeO Hf Ydj , GdTjQGRj GdHjVGhj, CHh SYjO CHh GdNjQ fGUQ GdOjf,J (B685 (3g` s
(3ChdgG (B:s
(3HYO GdHSedI Gdebhd ai Yde GdBOGH (B: (3gh Yde jYQa Hg GdJaGge YeG ai GdVeGFQ HBOdI GdCdaGX hGdcJGHI s
(3BNQgG (B:s
(3hefaYg VHW GdeYGedGJ hMaX GdCehGd hbSeI GdJQcGJ hZjQgG , hgh jMJGL Edjg ai SGFQ GdYdhe s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B110 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B298s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B416 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B738 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeg (B- (3U (B81 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdHdOjI HGScfOQjI (B(3018) s
Keywords: (3GdeYGQa GdYGeIs